Geographical karyotypic variations and chromosome banding patterns in tropidurus hispidus (Sauria, iguanidae) from brazil - Kasahara, Sanae [UNESP]; Yonenaga-Yassuda, Yatiyo; Rodrigues, Miguel Trefaut (Firenze University Press, 1987)
Karyotypic data are presented for Tropidurus hispidus (Sauria, Iguani-dae) collected at six different localities in Brazil. The specimens from all the populations share the same basic 2n = 36 karyotype characterized by 12 macrochromosomes and 24 microchromosomes. The X is an acrocentric microchromosome and the Y, a minute microchromosome. The mechanism of sex determination is of XX:XY type. Geographical karyotypic variations related to the presence or the absence of a prominent secondary constriction in one pair of macrochromosomes and to different sites of the nucleolar organizer regions (NORs) were found. Chromosome polymorphisms related to the size of the secondary constriction, the differential activity of NORs and the amount of constitutive heterochromatin were observed in specimens from some populations. G-and R-banding patterns were obtained for the first time in T. hispidus after «in vivo» treatment with 5-bromodeoxyuridine (BrdU). © 1987 Taylor & Francis Group, LLC.